2008
DOI: 10.1111/j.1365-2583.2008.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Semliki Forest virus strongly reduces mosquito host defence signaling

Abstract: The Alphavirus genus within the Togaviridae family contains several important mosquito-borne arboviruses. Other than the antiviral activity of RNAi, relatively little is known about alphavirus interactions with insect cell defences. Here we show that Semliki Forest virus (SFV) infection of Aedes albopictus-derived U4.4 mosquito cells reduces cellular gene expression. Activation prior to SFV infection of pathways involving STAT/IMD, but not Toll signaling reduced subsequent virus gene expression and RNA levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 75 publications
4
110
2
Order By: Relevance
“…We have recently reported that mild reduction of host gene expression also occurs in SFVinfected Ae. albopictus U4.4 cells (Fragkoudis et al, 2008). In this case, it also appears that host RNA synthesis is reduced early in infection (our unpublished observations).…”
Section: Virus Suppression Of Immune Signalling In Mosquito Cellsmentioning
confidence: 82%
See 1 more Smart Citation
“…We have recently reported that mild reduction of host gene expression also occurs in SFVinfected Ae. albopictus U4.4 cells (Fragkoudis et al, 2008). In this case, it also appears that host RNA synthesis is reduced early in infection (our unpublished observations).…”
Section: Virus Suppression Of Immune Signalling In Mosquito Cellsmentioning
confidence: 82%
“…In the case of another alphavirus, SFV, if activated before infection, not Toll-but Gram-negative-mediated signalling (JAK/STAT or Imd/Jnk) can inhibit virus replication in mosquito cell cultures (Fragkoudis et al, 2008). Bacterial infection also induces resistance to various RNA viruses in D. melanogaster, whilst the JAK/STAT pathway is a mediator of antiviral activities (Dostert et al, 2005;Teixeira et al, 2008).…”
Section: Immune Signalling In Response To Arbovirus Infectionsmentioning
confidence: 99%
“…Activated STAT acts as a transcription factor inducing expression of antimicrobial peptides (AMPs) such as two DENV restriction factors [115] and vir-1 [92]. However, treatment with poly I:C (a synthetic analogue of dsRNA) or BTV dsRNA did not lead to vago upregulation and STAT activation in C. quinquefasciatus cells [92], and infection of U4.4 cells with the alphavirus SFV did not lead to activation of STAT [33]. Taken together, these findings suggest that activation of STAT may be a specific anti-flaviviral response.…”
Section: Antiviral Responses Triggered By Innate Immunity Signallingmentioning
confidence: 99%
“…Taken together, these findings suggest that activation of STAT may be a specific anti-flaviviral response. However, replication of SFV was reduced when STAT was activated prior to SFV infection by treatment with heat-inactivated Escherichia coli bacteria [33]. Due to the concurrent activation of the Imd pathway, it could not be concluded if this was a specific consequence of JAK/STAT activation.…”
Section: Antiviral Responses Triggered By Innate Immunity Signallingmentioning
confidence: 99%
See 1 more Smart Citation